(untitled) (Altre Modernità, 2013)
The paper analyses a poem by Ernesto Cardenal, “Apocalipsis”, and a tale by Julio Cortázar, “Apocalipsis in Solentiname”. The first text presents the perspective of a possible nuclear war, the second uses the inexplicable metamorphosis of a serie of slides to denounce the crimes of latin american dictatures.